PEMBERDAYAAN MASYARAKAT DI DESA PENYANGGA TNWK DALAM MITIGASI BENCANA (STUDI KASUS DI DESA BRAJA KENCANA) - Utami, Anisa; Puspawati, Ani Agus; Caturiani, Susana Indriyati; Apandi, Apandi; Chairunnisa, Syaza; Anisa, Nur; Alfarisi, Muhammad Naufal (Magister Administrasi Publik FISIP Universitas Mulawarman, 2025)
Braja Kencana Village, a buffer village of Way Kambas National Park (TNWK) in East Lampung Regency, faces significant risks from natural disasters, especially forest fires and floods. The increase in the frequency and intensity of disasters, as well as exacerbated by climate change, requires a community-based disaster risk reduction program that can increase public awareness and readiness in disaster mitigation and response. This study aims to examine the process of community empowerment around TNWK in disaster mitigation, especially forest fires. This research method uses a qualitative approach with interviews, observations, and documentation to explore information from key informants such as village officials, members of the Forest Farmers Group (KTH), and members of the Polhut Partner Community (MMP). The results of the study show that community empowerment in Braja Kencana Village is carried out through three stages of empowerment, namely the awareness stage, the capacity stage, and the awareness stage. The awareness stage was carried out through effective socialization to KTH members about the importance of empowerment programs and how they can contribute. The capacity building stage includes various educational and socialization activities to improve community knowledge and skills in disaster mitigation. The empowerment stage is in the form of providing facilities from TNWK such as land and grass seeds for animal feed, as well as sustainable business development to increase the economic independence of the community.